Degradation properties of biodegradable polymers - Asraf, Nur Heena; Adli, Sarah Amalina; Barre, Mohamed Soleiman; Ali, Fathilah; Anuar, Hazleen (Zibeline International, 2019)
Plastics have been a fundamental need in our daily life and most of the plastics are petroleum-based, it cannot be degraded in the environment. Polylactic acid (PLA) is known as a biodegradable polymer and it can be a potential substitute for the petroleum-based plastics. However, PLA is known to be brittle and it has a slow degradation rate. Therefore, the aim of this study is to modify PLA in order to overcome the limitations and broaden its application in the packaging industry. In the present study, PLA is incorporated with different fillers (starch and nanocellulose) and plasticized with epoxidized palm oil (EPO) to further improve its properties and increase the degradation rate. Solvent casting method is used for the preparation of the composites. The samples prepared were subjected to a soil test for six months. Mechanical properties of the composites were evaluated by tensile testing. The weight loss of composites were recorded monthly and the composites blends undergo characterization analysis using Scanning Electron Microscopy (SEM). The utilization of polymer blend composites is the most suitable alternative to improve the properties of PLA to be used in various applications. After further analysis it can be concluded that starch acts as a better filler compared to nanocellulose with the presence of EPO in the composites.